Applying Theory of Planned Behavior to Understand Pro-Environmental Intention and Behavior of Students - Atif Aziz (Arthatama: Journal of Business Management and Accounting, 2019)
The study aims to use the theory of planned behavior to examine the pro-environmental intention and behavior of the students of Jordanian universities and higher education institutes. Students participated in the study were selected based on non-probability purposive sampling technique. Using five-point Likert scale questionnaire, the study has gathered 319 responses. PLS-SEM using SmartPLS version 3.2.8 has been employed in the study for data analysis. The results of the study showed that attitude, subjective norm, and perceived behavioral control have significant effect on intention towards environmental responsible behavior of students while environmental awareness, perceived behavioral control, and intention have significant effect on pro-environmental behavior of students in Jordan. Our findings are beneficial for workplace recruiting and incentive-related companies. For instance, the intention-behavior result suggests that companies with influential environmental agendas will implement in-depth evaluation of specific environmental perceptions and motivation throughout the procurement phase.